Avaliação da função ventricular esquerda: comparação entre sequência de ressonância magnética com múltiplas apneias e sequência sem pausa respiratória e com número elevado de excitações - Nakano, Edson Minoru [UNIFESP] (2009)
Objective: to assess the performance of the magnetic resonance (MR) sequence with three excitations (3 NEX), to determine ventricular volumes and masses, in free breathing individuals, compared with RM sequence with multiple apneas. Methods: in 32 healthy volunteers, their left ventricular (LV) volumes and masses determined through two cine mode MR sequences were compared. The first one was the one traditionally used and considered standard, in apnea and with 1NEX. The second one, in free breathing and with NEX elevated to 3. Three readers, with different levels of experience, tested inter and intra-observer reproducibility and concordance. The statistical analysis was made using the intraclass correlation coefficient (ICC), T-test, Bland-Altman plots and Sign test. Results: the images obtained with 3 NEX sequences had inferior quality; however, for readers with experience and adequately trained, there was no damage to ventricular volumes and masses calculation. It was possible to verify an excellent correlation and concordance in regard to the standard sequence (in apnea), with intraclass correlation coefficient above 0.913, T-test descriptive levels above 0.05, Bland-Altman plots presented differences randomly distributed around zero and Sign test descriptive levels above 0.05. Conclusion: the 3 NEX sequence presents an excellent reproducibility and concordance in regard to the standard sequence, in apnea, as traditionally used.